(untitled) (Applied Biological Research, 2016)
Medicinal plants have tremendous potential for the development of new drugs molecule effective against various diseases. Genus Piper is the largest genus in family Piperaceae and indigenous to India with one of the most widely used spice in the world. Biotechnological innovations in Piper species have lead to the development of plant-derived molecules which exhibit a promising effect in therapeutics. The present paper reviews the genetic diversity analysis of major Piper species through DNA markers, to establish in vitro protocol for mass multiplication of elite clone of different species, phytochemical compounds extracted in various solvent systems in Piper species and comparative analysis of active compounds associated with Piper species through HPTLC analysis as well as testing their antimicrobial activities. The activity has been tested against bacteria like E. coli, Micrococcus luteus, Streptomyces epidermidis, etc. and fungi like Aspergillus niger, A. flavus and Rhizoctonia solani using agar well diffusion method. The review also highlights the use of in vitro strategy in genetic manipulation of transgenic traits using specific promoters to accomplish high tissue specific protein production and overcome biotic stresses.